The Role of Tourism Potential, Community Attachment and Infrastructure in Tourism Development in Tirah Valley, Khyber Pakhtunkhwa, Pakistan - Shahid Munir; Ihtisham ul Haq; Hassan Taj; Hameed Gul (International Journal of Business and Economic Affairs, 2025)
Tirah Valley, District Orakzai, has breathtaking landscapes, glaciers, snow-covered mountains and lush green meadows. Besides, the traditional house structures also can attract tourists but yet tourism is not developed here due to certain reasons. However, Tirah Valley would emerge as a tourist destination in Khyber Pakhtunkhwa, Pakistan. Therefore, this study examines the role of tourism potential, community attachment, and infrastructure in tourism development in Tirah Valley, Orakzai. The study collected 250 responses through a structured questionnaire and examined the data using structural equation modeling. Results revealed that tourism potential, community attachment, and infrastructure positively influence tourism development in Tirah Valley. Additionally, the study found tourism potential and infrastructure are the most influential factors of tourism development. Policy implications are suggested to develop Tirah Valley, Orakzai as a tourist destination.